English Learning in the Digital Age Agency, Technology and Context - Zeng, Shuang (Springer Singapore, 2018)
Moving beyond the 'Web 2.0' and 'digital native' rhetoric, this book addresses the complex experiences of learners of English as a foreign language (EFL) in a world embedded with interactive and participatory technologies. Adopting a sociocultural perspective, it investigates EFL learners' behaviours concerning digital technology, and guides exploration into their contextually mediated choices and learning practices in the '2.0' era. The argument is developed on the basis of the findings of a mixed sequential study that focused on 1485 Chinese undergraduates' use and non-use of online tools and applications outside the English classroom. Particular attention is paid to the role of context and agency when understanding their learning choices and behaviours in the context of digital technology. In particular, the book acknowledges the explanatory power of agency in the minority instances of 'good practices' among these EFL learners. At the same time it demonstrates that for most learners, use of the current web is limited and mostly non-interactive. The barriers to '2.0' transfer are largely contextual and the so-called 'communicative opportunities' and 'participatory culture' in particular did not fit into the learners' sociocultural context of (language) learning. Overall, the compelling argument proposes that the technology-facilitated changes in EFL practices are a 'bottom up' process that is taking place in day-to-day situations and constrained by the learning context within which the learner is situated. Based on these arguments, the book provides a framework that challenges the existing beliefs about (language) learning with online technology, and that contributes to our understanding of how context mediates EFL learners' behaviours surrounding digital technologies. It is a valuable resource for teachers, researchers and policy makers, providing them with insights into using digital technology to stimulate 'good learning practices' outside the classroom.